Dark calories eaudiobook How vegetable oils destroy our health and how we can get it back. - Shanahan, Catherine (2024)
The New York Times bestselling author of Deep Nutrition explains how a group of eight little-known oils cause the cellular damage that underlies virtually all chronic disease, exposes the corruption that deceives doctors and consumers into eating them, and gives us a clear roadmap to recovery and rejuvenation. Did you know that eating a large serving of french fries—cooked in vegetable oil—delivers the toxicity of smoking 24 cigarettes? Cornell-trained biochemist turned family physician Dr. Cate Shanahan introduces us to well-respected scientists who warn that vegetable oils are a public health disaster, wreaking havoc on our bodies' cells by depleting antioxidants and promoting free radical toxicity. Their many effects include: Uncontrollable hunger, so we need drugs to maintain our weight Inflammatory fat buildup under our skin and within our internal organs and arteries Blood sugar swings that promote bad moods and antisocial behavior Disrupted brain energy, concentration problems, and mental illnesses Intracellular oxidative stress that promotes cancer development Gut inflammation, bloating, heartburn, and the runs Americans were enticed into buying these oils based on their cholesterol-lowering property, but the idea that cholesterol-lowering is beneficial was pushed on us without solid evidence to support it. In Dark Calories , Dr. Cate reveals the financial entanglements between industry and underhanded academics who created and sustain our 1950s-era, arbitrary dietary rules. As a solution, she proposes a clear, no-nonsense plan that aligns with our genetic needs and nature's laws. Thankfully, recovering our health is simplified by the fact that nutrients that treat one condition also tend to treat all the rest. As an added bonus, we also revive our sense of taste so that our cravings shift to wholesome, nourishing foods instead.